Instrument adaptation and validation to evaluate psychosocial skills and healthy habits in schoolchildren - Niño-Bautista, Lucila; Hakspiel-Plata, María Constanza; Mantilla-Hernandez, Laura Cristina; Cardenas-Herrera, Mary Stella; Guerrero-Parra, Nury Constanza (Universidad y Salud, 2017)
Objective: To adapt and validate an evaluation tool on psychosocial skills for life and healthy habits in Schoolchildren from a locality in Bogota, Colombia. Materials and methods: This quantitative transversal with empirical analytical non-experimental approach study evaluated responses of schoolchildren in third and fourth grade of primary school with the instrument adapted and reconstructed to establish technical quality of items, reliability and validity of it. The instrument (18 psychosocial skills and 19 healthy habits, plus 4 identification items) was self-diligence with Yes, No dichotomous answer option. It had evidence of apparent validity with schoolchildren from other peer institutions and was tested at 32 Public schools and analyzed using the Rasch model. Results: 1,066 schoolchildren participated in total. The items of the two constructs showed a good fit to the Rasch model as well as unidimensionality, reliability and separation measures above the recommended values. There was no differential functioning of the item by sex. Conclusion: The instrument of 37 items presented good properties of validity, reliability and adjustment to Rasch; although it does not have enough items of high difficulty level, which can be corrected in future applications.